From Digital Discovery to Offline Conversion: The Role of Google Business Profile in Driving Consumer Emotions, Visit Intention, and Purchase Intention among Cafés in Bandung - Fitriani, Novi (Universitas Serang Raya, 2025)
This research looks at how Google Business Profile (GBP) makes people want to go to and buy from coffee shops, using the Pleasure–Arousal–Dominance (PAD) Theory, the Theory of Planned Behavior (TPB), and the Quality–Intention Framework. Information gathered from surveys of 226 users was examined using a method called partial least squares structural equation modeling (PLS-SEM) to understand how feelings and thoughts affect what people plan to do. The findings show that what GBP looks like affects people's feelings and what they think, which then makes them want to do things in the real world. By combining PAD, TPB, and ideas about quality and intentions, this study gives a new way to understand how finding things online through GBP turns into what people do in person. Key words: Google Business Profile, PAD Theory, Theory of Planned Behavior, Quality–Intention Framework, Purchase intention, Café industry Paper type Research paper